Water use efficiency and nutrient uptake of rice under soil water stress condition - Purbajanti, Endang; F, Kusmiyati; Fushkah, Eny (Jurnal Online Pertanian Tropik, 2020)
One obstacle that can limit the growth and production of rice is low water availability. Therefore, a comprehensive study of the response of rice plants to drought is very important. The study was conducted in the greenhouse of the Faculty of Animal Husbandry and Agriculture, Diponegoro University, from April to August 2016. The study used a 3 x 3 factorial design with 3 replications. The first factor is three types of rice (Sidenuk, Way Apo Buru, Pepe) and the second factor is water stress treatment (KA <field capacity = enough water, field capacity (KL), water saturation (JA). The observed parameters are protein content, leaf levels rolling (number of leaves rolled), relative water content (RWC), water use efficiency (WUE),Â  N, P, K uptake, rice protein content decreases with increasing water supply. The relative water content of rice plants decreases with increasing stress water that occurs in the limited water supply for the three types of rice Sidenuk rice has the lowest N seed content (2.1%) compared to Way Apo (3.0%) and Pepe (3.1%). The mineral content of P in both biomass and seeds is not really influenced by water stress, as well as K content of seeds. Â  REFERENCES Badan Pusat Statistik. 2018. https://www.bps.go.id/dynamictable/2019/04/15/1608/luas-panen-produksi-dan-produktivitas-padi-menurut-provinsi-2018.html Darwesh, R, S,S. 2013. Improving growth of date palm plantlets grown undersalt stress with yeast and amino acids applications Annals of Agricultural Science (2013) 58(2), 247â€“256 Etienne P.I.D,Â  S. Diquelou , M. Â Prudent, C. Salon., A. Maillard, andÂ  A.Ourry. 2018. Macro and Micronutrient Storage in Plants and Their Remobilization When Facing Scarcity: The Case of Drought. Agriculture 2018, 8, 14; 2-17. doi:10.3390/agriculture8010014 Farooq, M., S.M.A.Basra, A. Wahid,Â  Z.A.Cheema, M.A.Cheema, A.Khaliq. 2008. The physiological role of exogenously applied glycine betaine in improving drought tolerance of fine grain aromatic rice (Oryza sativa L.).Journal of Agronomy & CropÂ  Science, 194: 325-333. Fitter, A.H.dan R.K.M. Hay. 1991. Fisiologi lingkungan tanaman. Gadjah Mada University Press, Yogyakarta Gholinezhad, E., A.Ayanaband, A. H. Ghorthapeh, G.Noormohamadi, I.Bernousi.2009. Study of the Effect of Drought Stress on Yield, Yield Components, and Harvest Index of Sunflower Hybrid Iroflor at Different Levels of Nitrogen and Plant Population. Not. Bot. Hort. Agrobot. Cluj 37 (2) 2009, 85-94 Kivuva, B.M. , S.M. Githiri, G. C. Yencho, J.Sibiya.2015. Screening sweet potato genotypes for tolerance to drought stress. Field Crops Research 171 (2015) 11â€“22 Jaleel CA, Manivannan P, Wahid A, Farooq M, Al-Juburi H J, Somasundaram R, Panneerselvam R. 2009. Drought stress in plants: A review of morphological characteristics and pigment composition. Int J Agric Biol, 11: 100â€“105. Nazar, R., S. Umar, N.A. Khan, O. Sareer. 2015. Salicylic acid supplementation improves photosynthesis and growth in mustard through changes in proline accumulation and ethylene formation under drought stress. South African Journal of Botany 98 (2015) 84â€“94. Nio, S.A. dan A.A. Lenak. 2014. Penggulungan daun pada tanaman monokotil saat kekurangan air. Journal Bio Logos, Agustus 2014, Vol.2, No 4: 48-55. Nuryani, S.H.U., Haji,M., Widya, N. Y., 2010. Serapan hara N,P,K pada tanaman padi dengan lama penggunaan pupuk organic pada vertisol Sragen. Jurnal Ilmu Tanah dan Lingkungan vul 10 No 1 : 1-13 Oh, M.W., and S. Komatsu. 2015. Characterization of proteins in soybean roots under flooding and drought stresses. Journal of Proteomics. 114 (2015): 161-181. Pandey, V., and Â A.Shukla.2015.Acclimation and Tolerance Strategies of Rice under Drought Stress.Â Â  Rice Science, 2015, 22(4): 147-.161. Penny-packer, B. W., K. T. Leath., W. L. Stout, and R. R. Hill. 1990. Technique for stimulating field drought stress in the greenhouse. Agr. J. 82 (5): 951â€“957. Purbajanti, E.D., F. Kusmiyati, and E. Fuskhah. 2017. Growth, Yield, and Physiological Characters of Three Types of Indonesian Rice Under Limited Water Supply. Asian J. Plant Sci., 16 (2): 101-108, 2017. Shi, G., S. Xia., J. Ye,Â  Y. Huang, C. Liu, Z. Zhang .2015. PEG-simulated drought stress decreases cadmium accumulation in castor bean by altering root morphology. Environmental and Experimental Botany 111 (2015) 127â€“134. Shao H B, L.Y.Chu, M.A. Shao, C.A.Jaleel, H.M. Mi. 2008. Higher plant antioxidants and redox signaling under environmental stresses. Comp Rend Biol, 331: 433â€“441. Steel,Â Â Â  R.G.D., andÂ Â Â Â  J.H.Â Â Â Â  Torrie,Â Â Â Â  1960.Â Â Â  Principles and Procedures of Statistics. McGraw-Hill, New York, USA. Suryanti, S., D. Indradewa, P. Sudira, J. Widada. 2015. Water Use, Water Use Efï¬ciency, and Drought Tolerance of Soybean Cultivars. AGRITECH, Vol. 35, No. 1, February 2015: 114-120. Wu,X.Â  and W. Bao. 2011. Leaf Growth, Gas Exchange and Chlorophyll FluorescenceParameters in Response to Different Water Deficits in Wheat Cultivars. Plant Prod. Sci. 14(3): 254â€•259 (2011) Zhang,Â Â  X.,Â Â Â  X.Â Â Â  Chen,Â Â Â  Z.Â Â  Â Wu,Â Â  X.Â Â  Zhang,Â Â  C.Â Â  HuangÂ  and M. Cao,Â  2005.Â  AÂ  dwarf wheat mutant is associated with increased drought resistance and altered responses to gravity.Â  Afr.Â Â  J.Â  Biotechnol., 4: 1054-1057. Zou L., X.Sun, Z. Zhan, P. Li, J. Wu, Tian Cai-juan, Qiu Jin-long, Lu Tie-gang (2011) Leaf rolling controlled by the homeodomain leucine zipper class IV gene Roc5 in rice. Plant Physiology 156:1589â€“ 1602